Menakar Kesahihan Matan Hadis: Telaah atas Shādh dan ‘Illah - Efendi, Rosyid; Rani; Anam, Saichul (Journal of Hadith Studies, 2022)
The study of hadith in the Islamic scientific tradition so far tends to give a larger portion to the sanad aspect than the matan. As a result, criticism of matan hadith is less methodologically developed. In fact, matan is the core of the substance of the hadith that determines the main meaning and message. The validity of matan is very crucial in maintaining the integrity of Islamic teachings. The two main loci in matan criticism that are often used as indicators of defects are shādh and 'illah. However, the implementation of criticism of these two elements has not been standardized in a consistent and structured evaluative system. This article aims to explore the principles of the validity of matan hadith according to classical and contemporary scholars, with a primary focus on the elements of shādh (irregularities) and 'illah (hidden defects). This study uses a qualitative approach with a literature study method. Data sources are taken from methodological literature such as the works of Ajjāj al-Khaṭīb, Nūr al-Dīn Itr, Shuhudi Ismail, as well as contemporary thought on the criticism of matan hadith. The results show that although the conditions for the absence of shādhz and 'illah are widely known, the practice of matan criticism is often still intuitive and not based on a solid methodological framework. This article finds that many matan hadiths that are considered valid because their sanad are strong, but they are substantially problematic, either because they contradict the Qur'an, common sense, and historical context. This study recommends six practical steps for matan criticism: (1) verification of sanad, (2) linguistic analysis, (3) inter-matan muqāranah, (4) content analysis, (5) maqāṣid al-syarī'ah approach, and (6) contextualization through asbāb al-wurūd. This approach is expected to be a more objective, scientific, and relevant system of eye criticism in answering contemporary challenges.